(untitled) (Revista Lusófona de Educação, 2025)
A proposal for intercultural Mathematical Education aims to articulate different cultural contexts in the process of teaching and learning Mathematics. Based on the foundations of Ethnomodelling, this theoretical article proposes a reflection on this educational perspective. In this scenario, the concept of Ethnomodelling and ethnomodels is presented, highlighting their possible contributions to the development of an intercultural Mathematical Education. Understood as a theoretical-methodological construct, Ethnomodelling is configured as an innovative approach that interconnects the fields of Ethnomathematics and Mathematical Modelling. Through the development of ethnomodels, the aim is to promote dialogue between different systems of mathematical knowledge, favoring intercultural comparison. Keywords: Ethnomathematics. Ethnomodels. Interculturality.